Treatment evaluation of flow-limiting stenoses of the superficial femoral and popliteal artery by parametric color-coding analysis of digital subtraction angiography series - Kostrzewa, Michael; Kara, Kerim; Pilz, Lothar R.; Müller-Mürtz, Hannelore; Rathmann, Nils-Andreas; Schönberg, Stefan; Diehl, Steffen J. (CardioVascular and interventional radiology, 2017)
Purpose: To evaluate the hemodynamic effect of percutaneous transluminal intervention (PTI) on stenosis of the superficial femoral (SFA) and popliteal arteries (PA) using time-density curves (TDCs) derived from digital subtraction angiography (DSA) series in correlation with ultrasound peak systolic velocity ratio (PSVR) and ankle brachial index (ABI). Materials and Methods: DSA series of SFA or PA of patients with symptomatic peripheral arterial occlusive disease was obtained with a flat-panel angiography system with intention-to-treat. In DSA series acquired before and after PTI, TDCs were analyzed proximal and distal of each stenosis using parametric color coding (PCC). For correlation, ABI and PSVR measurements pre- and post-PTI were recorded for all patients. Results: In total, 25 stenoses of the SFA or PA were treated by PTI in 22 patients (17 male, 5 female, mean age 68 years). After treatment, peak-to-peak (PTP) times between TDCs proximal and distal to the treated vessel segment decreased statistically significantly (p = 0.01) on average from PTP = 1.9 ± 1.7 s to mean PTP = 1 ± 1 s. ABI and PSVR also changed statistically significantly after treatment (pretreatment ABI = 0.7 ± 0.2, PSVR = 4.2 ± 1.9; post-ABI = 0.9 ± 0.2, PSVR = 1.3 ± 0.4, both p < 0.05). Correlation parameters did not show a strong correlation between change in TDC and clinical parameters ABI and PSVR. Conclusion: Using PCC for analyzing contrast medium dynamics in DSA series is clinically useful for evaluating stenoses of the SFA and PA and for immediate treatment control after PTA. Level of Evidence: Case series, IV